(3TLQI Gdjbjfs - (3CHh GdMSf GdGTYQjs
(3ChdgG (B:s
(3hbO LGA ai GdNHQ Cf Gddg JYGdi Ndb TLQI dgG CQHYI CZUGf aSeGgG TLQI Gdjbjf Ke Ndb fhQ eMeO Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hced MLc HRjGQI SjO GdeQSdjf Udi Gddg Ydjg hYdi Bdg hCUMGHg hNJe Gddg dfG hdc HGdMSfi EfJgJ HMeO Gddg JYGdi hMSf Yhfg hJhajbg GdLejd s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3fSNI ecQQI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds